Unraveling transboundary water security in the arid Americas - Albrecht, Tamee R. (2018)
Transboundary waters are characterized by diverse and complex socio-politico-economic obstacles to effective water management. We examine five distinct cases in the arid Americas–in locations from the US–Mexico border to the Andes mountains–employing water security as a conceptual prism to unravel the multiple and varied attributes of transboundary water challenges. We describe how borders complicate water security in arid regions and explore how institutional arrangements and practices–within and across jurisdictions–respond to these challenges. We find that institutional capacity is needed on multiple levels for effective water management, and institutions must be responsive and flexible to change.